2019
DOI: 10.1039/c9py01216h
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a conjugated/elastic block sequence on the morphology and electronic properties of polythiophene based stretchable block copolymers

Abstract: We report the synthesis, morphology, and electronic properties of intrinsically stretchable AB-type, ABA-type, and BAB-type block copolymers (BCPs) of poly(3-hexylthiophene) (P3HT: A block) and elastic poly(octylene oxide) (POO: B block).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 51 publications
1
29
0
Order By: Relevance
“…For TBCs of P3HT and poly(octylene oxide), it was found that while the former sequence had a slightly lower modulus (159 MPa compared to 195 MPa), it also had a much reduced stretchability, and a mobility that was one order of magnitude lower (7.5 × 10 −5 cm 2 V −1 s −1 –2.5 × 10 −4 cm 2 V −1 s −1 ). [ 29 ] End‐capping P3HT with poly(δ‐decanolactone) gives a TBC with 8.5 × 10 −3 cm 2 V −1 s −1 but a high modulus of 1.46 GPa, and under 100% strain, only 9% of the mobility is retained. [ 30 ]…”
Section: Figurementioning
confidence: 99%
“…For TBCs of P3HT and poly(octylene oxide), it was found that while the former sequence had a slightly lower modulus (159 MPa compared to 195 MPa), it also had a much reduced stretchability, and a mobility that was one order of magnitude lower (7.5 × 10 −5 cm 2 V −1 s −1 –2.5 × 10 −4 cm 2 V −1 s −1 ). [ 29 ] End‐capping P3HT with poly(δ‐decanolactone) gives a TBC with 8.5 × 10 −3 cm 2 V −1 s −1 but a high modulus of 1.46 GPa, and under 100% strain, only 9% of the mobility is retained. [ 30 ]…”
Section: Figurementioning
confidence: 99%
“…1) [16]. On the other hand, higher alkylene oxides, such as butylene oxide (M3) and octylene oxide (M4), can be polymerized using t-Bu-P 4 virtually without side reactions, producing the corresponding well-defined polyethers with narrow dispersity and predictable molecular weights [16,21,24]. A detailed study using M3 revealed the living nature of this polymerization system.…”
Section: Fundamental Aspects and Applicable Monomer Scope Of T-bu-p4-catalyzed Aropmentioning
confidence: 99%
“…Indeed, by taking advantage of the well-controlled nature of t-Bu-P 4 -catalyzed AROP, several groups, including ours, have successfully created polyetherbased or polyether-containing functional materials. Examples include thermoresponsive materials [39], solid electrolytes for lithium batteries [40], organic memory devices [24], antifouling materials [41], and polymeric micelles [26,27,42,43].…”
Section: Application To Functional Materials Synthesismentioning
confidence: 99%
“…7 It is already known that the present data storage technologies have technical weaknesses that position them for replacement by upcoming resistive data storage technology. [8][9][10] For example, HDDs drain battery life; and, although NAND (NOTAND) flash memory may offer nonvolatility, it suffers from slow writing speeds and a limited number of rewritable cycles. [11][12][13][14][15] Today's most promising alternative non-volatile memory technology is Resistive Memory, more precisely, Resistive Random-Access Memory (ReRAM), which is expected to inherit the market for NAND flash.…”
Section: Introductionmentioning
confidence: 99%